Parenting Style, Feeding Patterns, and Adolescent Eating Behavior in South Kalimantan between Male and Female Adolescents - Nurfitriliani Fitri; Dwi Hastuti; Lilik Noor Yuliati (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2019)
Parenting style and parenting eating patterns are a way of controlling teenagers eating behavior. This study aims 1) to analyze gender differences in adolescent characteristics, family characteristics, feeding patterns, and eating behavior; 2) to analyze the effect of adolescent characteristics, family characteristics, and feeding patterns on adolescent eating behavior. This study used a cross-sectional study design with survey methods. The sample of this study was 160 adolescents (61 boys and 99 girls who were in grade 10 of high school). The results of the T-test showed that there were no significant gender differences in adolescent characteristics and family characteristics. There were significant differences in authoritarian parenting style, feeding patterns and eating behavior between boys and girls. The results of the regression analysis showed that eating behavior was influenced by age and feeding patterns.